A few aspects of well-known Athenian ISONOMIA in Ancient Greece and its opposition to the profession of a logographer - Tuszyńska, Krystyna (Scripta Neophilologica Posnaniensia, 2018)
A few aspects of well-known Athenian ISONOMIA in Ancient Greece and its opposition to the profession of a logographer